Training method for a feed forward neural network based on meta-heuristics - Melo, H. (Springer Science and Business Media Deutschland GmbH, 2018)
This paper proposes a Gaussian-Cauchy Particle Swarm Optimization (PSO) algorithm to provide the optimized parameters for a Feed Forward Neural Network. The improved PSO trains the Neural Network by optimizing the network weights and bias in the Neural Network. In comparison with the Back Propagation Neural Network, the Gaussian-Cauchy PSO Neural Network converges faster and is immune to local minima. Â© Springer International Publishing AG 2018.